Effect of potassium fertilization on storage root number, yield, and appearance quality of sweet potato (Ipomoea batatas L.) - Liu, Ben-kui; Xv, Bing-jie; Si, Cheng-cheng; Shi, Wen-qing; Ding, Guo-zheng; Tang, Li-xue; Xv, Ming; Shi, Chun-yv; Liu, Hong-jvan (Frontiers in Plant Science, 2024)
Increasing storage root number is a pivotal approach to enhance both storage root (SR) yield and appearance quality of sweet potato. Here, 2-year field experiments were conducted to investigate the effect of 0 (K0), 120 (K1), 240 (K2), and 360 (K3) kg ha−1 potassium fertilizer (K2O) on lignin metabolism, root growth, storage root yield, and uniformity. The results demonstrated that potassium (K) application led to a decrease in the activities of key enzymes involved in lignin biosynthesis, including phenylalanine deaminase (PAL), 4-coumarate coenzyme A ligase (4-CL), cinnamic acid dehydrogenase (CAD), polyphenol oxidase (PPO), and peroxidase (POD). This resulted in a significant reduction in lignin and G-type lignin contents in potential SRs compared to K0 treatment within 10–30 days after planting (DAP). BJ553 exhibited a significant decrease in PAL activity, as well as lignin and G-type contents at 10 DAP, whereas YS25 showed delayed effects until 20 DAP. However, the number and distribution of secondary xylem conduits as well as the mid-column diameter area in roots were increased in K2 treatment. Interestingly, K2 treatment exhibited significantly larger potential SR diameter than other treatments at 15, 20, and 25 DAP. At harvest, K2 treatment increased the SR number, the single SR weight, and overall yield greatly compared with K0 treatment, with an average increase of 19.12%, 16.54%, and 16.92% respectively. The increase of SR number in BJ553 was higher than that of YS25. Furthermore, K2 treatment exhibited the lowest coefficient of variation for both SR length and diameter, indicating a higher yield of middle-sized SRs. In general, appropriate potassium application could effectively suppress lignin biosynthesis, leading to a reduction in the degree of pericycle lignification in potential SRs. This promotes an increase in the number of storage roots and ultimately enhances both yield and appearance quality of sweet potato. The effect of potassium fertilizer on lignin metabolism in BJ553 roots was earlier and resulted in a greater increase in the SR number compared to YS25.